COMPARISON OF FENTON 2013 AND INTERGROWTH-21ST GROWTH CHARTS IN ASSESSING NEONATAL GROWTH PATTERNS AND OUTCOMES IN A TERTIARY NICU IN INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Preterm and low-birth-weight infants are often assessed using standard growth charts. The Fenton 2013 chart, based on retrospective data from developed countries, and the INTERGROWTH-21st (IG-21st) chart, based on multiethnic prospective data, are commonly used standards. This study compares neonatal growth patterns using both charts and examines associated morbidities.Materials and Methods: We conducted a prospective observational study in the neonatal intensive care unit (NICU) of Sri Guru Ram Das Institute of Medical Sciences (July 2024–Dec 2025). All inborn and outborn neonates (gestational age 24–40 weeks) admitted within 24 h of life were enrolled after informed parental consent. Exclusions: major congenital anomalies or lost to follow-up. Weight, length, and head circumference were recorded at birth and periodically until discharge, and plotted on Fenton 2013 and IG-21stcharts. Neonates were classified as small for gestational age (SGA;